A narrow Heliconius cydno (Nymphalidae; Heliconiini) hybrid zone with differences in morph sex ratios (2005)
In the western cordillera of the Cauca valley, Colombia, there is a narrow hybrid zone between two races of Heliconius cydno , one of which is polymorphic. Three large broods show that most of the phenotypic variation observed can be explained by four loci of major effect, named Sb , Yb , L, and K . Two further loci, G and Wo , were identified that control more minor phenotypic variation. Sb, Yb, and Wo are linked and the latter is differentially expressed between the sexes. The transition between H. c. cydnides in the north and H. c. weymeri to the south occurs over approximately 15 km. Collections from a single site near the center of the hybrid zone show that gene frequencies have been stable over the 10 yr from 1991 to 2001 and that color?pattern genes are in Hardy–Weinberg equilibrium, with little evidence for linkage disequilibrium. This suggests that mating is random between color?pattern forms. Nonetheless, there is evidence for variation in the sex ratio, with parental phenotypes and the most melanic hybrid phenotypes showing a fairly even sex ratio compared to a strong male bias observed in the remaining hybrids. We hypothesize that this might be explained by differential selection between sexes and phenotypes, phenomena that could have important implications for hybrid zone analysis and the evolution of Müllerian mimicry.